Penerapan Sanksi Denda terhadap Pelaku Pelanggaran Protokol Kesehatan Covid 19 - Reonaldo Charlos Pattipeilohy; John Dirk Pasalbessy; Elias Zadrach Leasa (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The government as a policy maker has made Covid-19 a non-natural national disaster.Purposes of the Research: Knowing and analyzing the inhibiting factors for the application of fines to perpetrators of health protocol violations.Methods of the Research: The research method used is normative legal research. With the approach used, namely the statute approach, and the conceptual approach.Findings of the Research: The findings of this study indicate that the inhibiting factors for the application of fines to perpetrators of violations of the COVID-19 health protocol in Ambon city are natural conditions that have an impact on the prevalence of violations, community economic factors that are the main concern when fines are imposed on violators and community dissatisfaction factors which often do not. receive when subject to fines which have implications for the delay in the application of fines.